Enhanced production of extracellular L-asparaginase in batch culture via nitrous acid-induced mutagenesis of Aspergillus oryzae - Sikander Ali; Sana Maqsood; Muhammad Usman Ahmad; Ifrah Shabbir; Mohammad Raish; Fozia Batool; Asad-ur-Rehman; Iram Liaqat; Bakar Bin Khatab Abbasi; Ali Irfan; Yousef A. Bin Jardan (Microbial Cell Factories)
Abstract Background L-Asparaginase (LA) is an important enzyme with therapeutic and industrial applications, particularly in the treatment of leukemia. Enhancing its production through optimization and strain improvement is crucial for commercial viability. This study aimed to increase LA production using Aspergillus oryzae by optimizing process parameters and employing chemical mutagenesis for strain improvement. Results Among thirty-five fungal strains isolated from soil, ISL-3 A. oryzae and ISL-9 A. niger were identified as the most efficient LA producers. Using sugarcane bagasse as a substrate for solid-state fermentation, process optimization revealed that ISL-3 showed 12.15% higher yield than ISL-9 under the conditions of 5 g substrate level, 9 mL diluent MC-5, and 72 h of incubation. Chemical mutagenesis using nitrous acid resulted in the mutant NA-t3 with LA activity of 4.479 ± 0.22 U/g, significantly surpassing the parent strain. Inducible resistance was achieved on NA-cysL-C4 with 8 ppm L-cysteine HCl. Supplementation with MgSO4·7H2O (3 mM), ammonium nitrate (0.2%), and 2-mercaptoethanol (0.125%) further enhanced LA activity. The final mutant strain’s yield increased to 16.122 ± 0.81 U/g, 2.07 times greater than the parent strain. Partial purification through ammonium sulfate precipitation (35–85%), dialysis, and chromatography achieved a 47% recovery yield, with SDS-PAGE confirming a molecular weight of 120 kDa for both strains. Conclusion The study successfully enhanced LA production from Aspergillus oryzae through process optimization and strain improvement using chemical mutagenesis. The significantly higher yield from the mutant strain makes it a promising candidate for commercial enzyme production. ANN was also employed on results to develop a correlation between experimental and predicted results. These findings highlight the potential of optimized solid-state fermentation and genetic enhancement techniques in industrial-scale.